(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Patient satisfaction is an important indicator reflecting the quality of healthcare services, in which communication and behavior of healthcare workers play a key role, especially in outpatient care.Objective: To assess the level of satisfaction and factors associated with outpatient satisfaction regarding communication and behavior of healthcare workers. Methods: A cross-sectional descriptive study was conducted on 220 outpatients. Data were collected using a structured questionnaire and analyzed using appropriate medical statistical methods. Results: The proportion of patients who were very satisfied and satisfied accounted for 91.4%, of which 63.7% were very satisfied. Factors significantly associated with patient satisfaction included gender (female: 87.1% vs. male: 73.9%; p<0.05), health insurance status (insured: 86.7% vs. uninsured: 63.8%; p<0.05), and number of visits (≥2 visits: 85.3% vs. <2 visits: 71.9%; p<0.05). Conclusion: Outpatient satisfaction with healthcare workers’ communication and behavior was high and was influenced by several personal and service-related factors. Continuous improvement in communication skills and professional attitudes of healthcare workers is necessary to further enhance service quality and patient satisfaction.